2015
DOI: 10.5539/ijef.v7n2p280
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Factors and Working Capital Requirement

Abstract: The objective of the current study is to investigate the various factors determining the working capital requirements in Pakistani non-financial firms by taking into account different economic and financial variables relating to the business over a period of six years (2004)(2005)(2006)(2007)(2008)(2009). The present study is anticipated to add to improve understanding the financial and non-financial firm related factors that form up working capital requirements of firms in the emerging markets like Pakistan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
2
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 7 publications
(7 reference statements)
6
9
2
8
Order By: Relevance
“…The study found that operating cycle, return on assets, leverage, size and level of economic activity is negatively related to working capital requirements of a firm where as operating cash flows and sales growth are positively related to working capital requirements. [11] A study of Nazir, M & Afza, T Working capital requirement and the determining factors in Pakistan by employing a study of 132 manufacturing firms from 14 industrial groups that were listed on Karachi Stock Exchange (KSE) between the periods 2004-2007 was undertaken. The pooled panel regression model result found that Leverage of a firm is strongly and negatively related to the working capital management of a firm, indicating that with a rising debt to total assets ratio, the firms are supposed to pay more attention to efficient management of working capital to avoid much more capital being tied up in account receivables and inventories.…”
Section: Empirical Literaturesmentioning
confidence: 99%
“…The study found that operating cycle, return on assets, leverage, size and level of economic activity is negatively related to working capital requirements of a firm where as operating cash flows and sales growth are positively related to working capital requirements. [11] A study of Nazir, M & Afza, T Working capital requirement and the determining factors in Pakistan by employing a study of 132 manufacturing firms from 14 industrial groups that were listed on Karachi Stock Exchange (KSE) between the periods 2004-2007 was undertaken. The pooled panel regression model result found that Leverage of a firm is strongly and negatively related to the working capital management of a firm, indicating that with a rising debt to total assets ratio, the firms are supposed to pay more attention to efficient management of working capital to avoid much more capital being tied up in account receivables and inventories.…”
Section: Empirical Literaturesmentioning
confidence: 99%
“…Bu bulgu Abbadi ve Abbadi (2013), AL-Taleb vd. (2010), Azeem ve Marsap (2015), Doğan ve Elitaş (2014), Gill (2011), Manoori ve Muhammad (2012 ile Palombini ve Nakamura'nın (2012) çalışmalarıyla benzerdir. Firmaların büyüklüğünün artmasıyla birlikte artan faaliyet hacmi, çalışma sermayesi oranını azaltarak, çalışma sermayesi ihtiyacını arttırmaktadır.…”
Section: B Bulgularunclassified
“…Penelitian terkait faktor determinasi dari kebutuhan modal kerja terdapat variasi hasil. Azeem & Marsap (2015) melakukan penelitian faktor determinasi kebutuhan modal kerja pada perusahaan non keuangan Pakistan dengan memperhatikan variabel-variabel ekonomi dan keuangan. Hasilnya menunjukkan bahwa siklus operasi, OCF, ROA, debt dan ukuran perusahaan signifikan terhadap kebutuhan modal kerja perusahaan.…”
Section: Modal Kerjaunclassified